Kad Hari Raya - Ali, Alias; -, Ramlah; Alias, Ramliza; Alias, Razli; Alias, Amiza
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Alias Ali, Ramlah serta Ramliza, Razli, Amiza